1991
DOI: 10.1507/endocrj1954.38.429
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Receptor Antibody Activities Significantly Correlate with the Outcome of Radioiodine (131I) Therapy for Hyperthyroid Graves' Disease.

Abstract: The outcome of 131I therapy for 109 patients with Graves' disease was analysed according to pretreatment laboratory data including thyrotropin receptor antibody (TRAb) activities. Forty-five percent of patients became euthyroid, and 13% of patients became hypothyroid within one year after 131I therapy. Forty-two percent of patients remained hyperthyroid one year after 131I therapy. Pretreatment values for serum T4, T3, and the estimated weight of the thyroid were significantly higher in the hyperthyroid group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
5
16
0
1
Order By: Relevance
“…Radioiodine therapy in patients with Graves' disease is indicated except for pregnant women and children when antithyroid medication cannot be continued due to its adverse effects [11,12]. In the case that the thyroid hormone level decreased to normal range after radioiodine therapy, there is the possibility of recurrence or hypothyroidism that may not be realized if the patient does not visit the hospital for follow-up examinations for some years and during follow-up the patients still consider themselves as having poorer health than the general population [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radioiodine therapy in patients with Graves' disease is indicated except for pregnant women and children when antithyroid medication cannot be continued due to its adverse effects [11,12]. In the case that the thyroid hormone level decreased to normal range after radioiodine therapy, there is the possibility of recurrence or hypothyroidism that may not be realized if the patient does not visit the hospital for follow-up examinations for some years and during follow-up the patients still consider themselves as having poorer health than the general population [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that males [3,4], younger patients [5,6], patients with more severe hyperthyroidism [5,6], patients with goiters of larger size [5][6][7][8][9][10][11][12], and patients with high TRAb value [11,12] were less likely to be cured after radioiodine therapy. Therefore it is possible to reduce the radioiodine dose for the other patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the gland was estimated by palpation. The therapeutic dose of 131 I was calculated using the following formula ( Kaise et al ., 1991 ; Aizawa et al ., 1995 ):…”
Section: Methodsmentioning
confidence: 99%
“…First of all, it is an autoimmune disorder, in which hyperthyroidism is caused by antibodies acting against thyrocytes, and not by the gland itself. This makes the choice of correct therapeutic activity of radioiodine fairly difficult [4]. What is more, because of increased vascularisation and greater metabolic activity of thyrocytes in GD, the turnover of radioiodine is usually accelerated during treatment [5].…”
Section: Prace Oryginalnementioning
confidence: 99%